Prognostic Value of Estimated Plasma Volume in Patients with Chronic Systolic Heart Failure. (February 2021) - Lin, Yuyao; Xue, Yanbo; Liu, Jing; Wang, Xiqiang; Wei, Linyan; Bai, Ling; Ma, Aiqun
Assessing congestion is challenging but important to patients with chronic heart failure (CHF). However, there are limited data regarding the association between estimated plasma volume status (ePVS) determined using hemoglobin/hematocrit data and outcomes in patients with stable CHF. We prospectively analyzed 231 patients; the median follow-up period was 35.6 months. We calculated ePVS at admission using the Duarte and Strauss formula, derived from hemoglobin and hematocrit ratios and divided patients into three groups. The primary outcome was a composite of all-cause mortality or heart failure rehospitalization. Among 274 patients (61.98 years of age, 2.3% male), the mean ePVS was 3.98±0.90 dL/g. The third ePVS tertile had a higher proportion of primary outcome (71.4%) than the first or second tertile (48.1% and 59.7%, respectively; p=0.013). On multivariable Cox analysis, after adjusting for potential confounders, higher ePVS remained significantly associated with increased rate of primary outcome (adjusted HR 1.567, 95% CI 1.267 to 1.936; p<0.001). Kaplan-Meier survival analyses showed that the occurrence of primary outcome, all-cause mortality and rehospitalization increased progressively from first to third tertiles (p=0.006, 0.014 and 0.001; respectively). In receiver operating characteristic analysis, the area under the curve of ePVS for primary outcome was 0.645. ePVS determined using hemoglobin and hematocrit was independently associated with clinical outcomes for patients with stable CHF. Our study thus further strengthens the evidence that ePVS has important prognostic value in patients with stable CHF. Trial registration number ChiCTR-ONC-14004463.